Optimizing irrigation efficiency and resilience: Advanced integration of SCH and SRI techniques for sustainable agricultural development and climate change mitigation - Andawayanti, Ussy; Hakim, Lukman; Lufira, Rahmah Dara (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Lempake Irrigation Area is one of the Irrigation Areas supporting rice barns in meeting food needs for the people in Samarinda City. The government continues to improve and maintain the Lempake irrigation area, but there is still a decrease in agricultural yields. This research aims to analyze the condition and performance of the irrigation system both physically and non-physically, then optimize the method of providing efficient and adaptive irrigation water to support sustainable agriculture. Methods: mode-median method to analyze irrigation water availability, then comparing SCH and SRI water application techniques to evaluate water use efficiency. Optimization of method selection was done using AHP and ANP with Super Decisions application. Results: Using the mode method, the maximum discharge occurred in period I in March, which was 519 l/second, and the minimum occurred in period II in October 29 l/second. The performance index value of the Lempake Irrigation Area irrigation network is 65.92% and is categorized as “less and needs attention”. With the existing water delivery method, the SCH K factor value of 1.58, the performance of the irrigation system is 65.92. Then if using the SRI water delivery method, the K factor value of 3.62 irrigation system performance increases to 80.14. Using the AHP method obtained ranking criteria that are prioritized in the proposed rehabilitation activities starting from physical conditions, human resource management, operating systems. Then with the ANP method obtained a ranking of channels in the Lempake Irrigation Network that gets priority in the proposed rehabilitation. Conclusion: in conclusion, the application of the SRI method of water application proved to be more efficient than the SCH method. Optimization of irrigation systems through more efficient methods can increase agricultural productivity in this region.